Analisis Efektivitas Implementasi Sistem Pembayaran Digital QRIS Dalam Meningkatkan Penjualan Usaha Dagang Plastik Intan Baru Sibuhuan - Ghilman Rozy Hrp; Nurbaiti Nurbaiti; Khairina Tambunan (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
QRIS is a breakthrough from Bank Indonesia as a means of integrating various types of digital payments into only one type of QR code. The purpose of this research is to find out whether the implementation of the QRIS digital payment system has been effective in increasing sales of the Sibuhuan New Diamond Plastic Trading Business. The method used in this study is a qualitative method with research subjects as business owners, employees and consumers who come to shop at UD Intan Baru Sibuhuan. The sampling collection technique is saturated and incidental sampling techniques through interviews, observation and documentation of shop owners and buyers. The location where this research was conducted was at the New Diamond Plastic Trading Business located in Sibuhuan City, Barumun District, Padang Lawas Regency. The research time lasted for 3 months, from December 2022 to March 2023. The results revealed that the implementation of the QRIS digital payment system was classified as effective. in increasing sales at UD Plastic Intan Baru Sibuhuan due to increased sales results and consumers feel the ease of transactions provided even though consumers using digital payments are still relatively minimal at UD Intan Baru Sibuhuan